Integrability and non-integrability for marginal deformations of 4d N $$ \mathcal{N} $$ = 2 SCFTs - Jitendra Pal; Sourav Roychowdhury; Arindam Lala; Dibakar Roychowdhury (Journal of High Energy Physics, 2023)
Abstract We study integrability and non-integrability for marginal deformations of 4d N $$ \mathcal{N} $$ = 2 SCFTs. We estimate various chaos indicators for the bulk theory which clearly shows the onset of a chaotic string dynamics in the limit of large deformations. On the other hand, for small values of the deformation parameter, the resulting dynamics exhibits a non-chaotic motion and therefore presumably an underlying integrable structure. Our analysis reveals that the γ-deformation in the type-IIA theory could be interpreted as an interpolation between a class of integrable N $$ \mathcal{N} $$ = 2 SCFTs and a class of non-integrable N $$ \mathcal{N} $$ = 1 SCFTs at strong coupling. We also generalise our results in the presence of the flavor branes.